2018
DOI: 10.1016/j.jab.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Red American ginseng enhances the effect of fluorouracil on human colon cancer cells via both paraptosis and apoptosis pathways

Abstract: Introduction: As a commonly used chemotherapeutic agent, fluorouracil (5-FU) has serious dose-limiting side effects. In this study, we evaluated the synergy between red American ginseng (RAG) and 5-FU on human colorectal cancer cells, and explored the potential mechanisms. Methods: Ginsenoside contents of white American ginseng (WAG) and RAG were determined by HPLC. Cell proliferation was evaluated by MTS assay. Combination Index (CI) analysis was executed using CompuSyn software. Paraptotic events were obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The design concept of amino acid uorescent probe is that considering the error of detection results caused by the toxicity of the probe itself, pyrimidine [32][33][34], which is widely used in the drug eld, is selected as the intermediate of targeting action to introduce the uorescent group BODIPY [35]. This design not only greatly reduces the toxicity problem of the probe, but also has certain drug activity in the overall structure.…”
Section: Resultsmentioning
confidence: 99%
“…The design concept of amino acid uorescent probe is that considering the error of detection results caused by the toxicity of the probe itself, pyrimidine [32][33][34], which is widely used in the drug eld, is selected as the intermediate of targeting action to introduce the uorescent group BODIPY [35]. This design not only greatly reduces the toxicity problem of the probe, but also has certain drug activity in the overall structure.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the various R 2 , the pyridine ring with an alkyliodine substituted at the para-position (5~12) exhibited better potency than non-substituted position (1~4). The para-substituted pyridine ring with a methyl (8) or propyl group (12) appeared to contribute concurrently to the potency. In contrast to the other analogs, 12 with aromatic ether substitution at R 1 also demonstrated good enzymatic potency.…”
Section: Evaluation Of Cytotoxicity Activity In Vitromentioning
confidence: 99%
“…[2][3][4][5][6] Cancer is a disease that is difficult to cure; it exhibits abnormal metabolic processes in living organisms for a variety of reasons, mainly due to various features, [7][8][9][10] such as complexity, diversification, and continuity. In many studies reported in recent years, a strategy to increase the apoptosis activity has been proposed, [11][12][13][14] and it was considered to be a potential cancer treatment method. This is a programmed cellular suicide process that removes damaged cells from multicellular organisms at the cellular level that is inactivated.…”
Section: Introductionmentioning
confidence: 99%
“…PQR is a medicinal and food homologous plant, widely used as dietary additives, has many benefits to human health, can effectively prevent and treat cancer diseases (Yu et al, 2015). Studies have shown that the anticancer active ingredients in PQR can be used as anticancer drugs alone (Yang et al, 2016), and can also be used in combination with other chemotherapy drugs to improve the efficacy or reduce the toxic and side effects (Wan et al, 2018).…”
Section: Anti-tumor Effectmentioning
confidence: 99%
“…In addition, in the treatment of colorectal cancer, when 5-FU combined with PQR, the cell proliferation inhibition rate was significantly increased. The ability of PQR to enhance the anticancer effect of 5-FU was related to apoptosis ( Wan et al, 2018 ). PQR could significantly enhance its anti-proliferation effect on a variety of cancer cells after being processed at high temperature, because the structure and composition of saponins were changed at high temperature, and more low-polarity saponins were produced, such as ginsenosides Rg3, 20R-Rg3, Rk1 and Rg5, etc.…”
Section: Physiochemical Compositionmentioning
confidence: 99%